A radar study of premonsoon squall lines over Gangetic West Bengal - CHAUDHURY , A. K.; RAKSHIT, D. K. (MAUSAM, 1970)
Occurrence and life cycle of premonsoon squall lines in Gangetic West Bengal, their dependence on the surfac6 and upper air meteorological parameters were analysed from other echoes observed at Calcutta for the period 1963-67. Presence of high terrain in Chota Nagpur plateau of Bihar and solar insolation found to be responsible for the initial formation of squall lines. The phenomenon leading to simultaneous appearance of multiple squall lines in different regions and their movement in different directions were discussed. It has been noticed that squall line move generally in a direction within 040° clockwise of the prevailing wind at 4.5-km level and the corresponding direction of surface squall observed to be within 020° of the direction of movement of squall line.